E-BANKING TRENDS IN INDONESIA: WHAT EVIDENCES SAY - Gunawan Widjaja (ADISAM Publisher, 2022)
This study aims to discuss the understanding of the phenomenon or trend of electronic banking in the country in terms of what the experts said through their studies from various perspectives and perspectives of banking and finance experts. This study relies on secondary data from book publications, scientific articles, and other data sources. We studied it under the phenomenological approach, which we started by mingling the question and then identifying the relevant literature. We continued by evaluating the suitability of the findings and the findings with the research problem, and finally, we tried to create a summary that could answer the problem validly and convincingly, and finally, we interpreted the funding obtained. We get, and we discuss. Finally, based on the data we got and the discussion we carried out in this study, we can conclude that the trend in Indonesian society to accept being a customer of electronic banking is due to the ability and innovation and effectiveness, and practicality of the services provided by banks, especially when a pandemic hits customers or the public, banking is electronics is one alternative solution that is very effective. Hopefully, this finding will be an addition to the complement of financial and banking studies in the future.